Interplay between light and circadian rhythms in the regulation of photoreception and physiological processes in the stony coral Acropora digitifera - Shi, Zongyan; Takemura, Akihiro (Frontiers in Marine Science, 2025)
Stony corals possess major components of the circadian system, which oscillate in response to light-dark cycles in aquatic environments. However, the extent to which the circadian system influences physiological processes remains unknown. This study investigated the role of circadian genes (cry1, cry2, cry3, clock, cycle, and slmb) in modulating the transcription of photoreceptor (opsin1, opsin2, and opsin3), calcification/metabolism-related (ca, pmca, sglt, and ppp1r), and homeostasis/stress-related (hif1α, egln, sod, and hsp70) genes in Acropora digitifera, a stony coral inhabiting shallow water. Nubbins of A. digitifera were reared under light-dark (LD) and constant darkness (DD) conditions and sampled at 4-h intervals. Quantitative PCR analysis revealed that cry1, cry2, cry3, and clock expression increased during the daytime under LD conditions and attenuated during the subjective daytime under DD conditions, suggesting that these genes are light-responsive. In contrast, cycle and slmb exhibited similar expression profiles with increases during the daytime/subjective daytime under both LD and DD conditions, implying robust roles in the circadian system. The abundance of opsin1 showed minimal change under LD and DD conditions, whereas the abundances of opsin2 and opsin3 increased during daytime/subjective daytime under both conditions, indicating circadian regulation. Some genes tested by qPCR significantly fluctuated with light (pmca, sglt, ppp1r, egln, sod, and hsp70) and time (ca, pmca, sglt, ppp1r, hif1α, egln, sod, and sod). Principal component analysis revealed significant correlations of circadian genes (cycle or slmb) with calcification/metabolism-related (pmca), oxygen homeostasis (hif1α), and stress indicator (sod) genes under both LD and DD conditions. Therefore, some physiological responses in A. digitifera exhibit daily changes and are partially regulated by the circadian system.